A strange thing happened in Cherry Hall - Warga, Jasmine (Harper, an imprint of HarperCollinsPublishers, 2024)
"A painting has been stolen...! When Rami sees a floating girl in the museum, he knows he has seen her somewhere before. Then he realizes: She looks just like the girl in the painting that has gone missing. But how does her appearance connect to the theft? Agatha the turtle knows -- she has been watching from the garden. But she can't exactly tell anyone...can she? Will Rami, with the help of his classmate, Veda, be able to solve the mystery? The clues are all around them, but they'll have to be brave enough to really look." --